2021
DOI: 10.1101/2021.05.12.443894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A behavioral screen for mediators of age-dependent TDP-43 neurodegeneration identifies SF2/SRSF1 among a group of potent suppressors in both neurons and glia

Abstract: Cytoplasmic aggregation of Tar-DNA/RNA binding protein 43 (TDP-43) occurs in 97 percent of amyotrophic lateral sclerosis (ALS), about 40 percent of frontotemporal dementia (FTD) and in many cases of Alzheimers disease (AD). Cytoplasmic TDP-43 inclusions are seen in both sporadic and familial forms of these disorders, including those cases that are caused by repeat expansion mutations in the C9orf72 gene. To identify downstream mediators of TDP-43 toxicity, we expressed human TDP-43 in a subset of Drosophila mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Two hits were recently identified in an independent genome‐wide screen in TDP‐43‐expressing flies and correspond to fly homologues of ARIDB1 and WAPL, 38 confirming their specificity. MED23 is relevant because subunits of the Mediator complex suppressed TDP‐43 toxicity in another screen 39 and interact with WAPL, 40 suggesting its importance in disease pathogenesis. TUBB2A transcripts were dysregulated in the axonal compartment of TDP‐43‐depleted motor neurons 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Two hits were recently identified in an independent genome‐wide screen in TDP‐43‐expressing flies and correspond to fly homologues of ARIDB1 and WAPL, 38 confirming their specificity. MED23 is relevant because subunits of the Mediator complex suppressed TDP‐43 toxicity in another screen 39 and interact with WAPL, 40 suggesting its importance in disease pathogenesis. TUBB2A transcripts were dysregulated in the axonal compartment of TDP‐43‐depleted motor neurons 41 .…”
Section: Discussionmentioning
confidence: 99%
“…The protein SRSF1 (Serine/Arginine-Rich Splicing Factor 1, also known as ASF/SF2) is essential for the early-stage assembly of the spliceosome (15,16). Several in vivo studies have shown that SRSF1 is found in condensates (5,(17)(18)(19)(20)(21)(22). Aberrant condensation behaviors have also been observed in disease states (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Several in vivo studies have shown that SRSF1 is found in condensates (5,(17)(18)(19)(20)(21)(22). Aberrant condensation behaviors have also been observed in disease states (20)(21)(22). SRSF1 belongs to the Ser/Arg-rich protein family (SR proteins), which contains 12 members possessing one to two structured RNA-recognition motifs (RRMs) and a repetitive Arg/Ser repeat region (RS domain) (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Models of TDP-43 proteinopathy in Drosophila have recapitulated the locomotor phenotypes, motor neuron dysfunction, and shortened lifespan (Estes et al, 2011;Li et al, 2010;Romano et al, 2012) observed in ALS and highlighted degeneration in central brain structures (Li et al, 2010) reminiscent of FTD. Beyond simply simulating disease states, these fly models have identified translational targets (Coyne et al, 2017;Coyne et al, 2014;Lehmkuhl et al, 2021) and genetic modifiers of TDP-43 proteinopathy (Azpurua et al, 2021;Coyne et al, 2015;Sreedharan et al, 2015;Zhan et al, 2013), and exposed systemic effects on metabolic pathways (Loganathan et al, 2022;Manzo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%